Simulation-Based Usability Evaluation of Spoken and Multimodal Dialogue Systems - Hillmann, Stefan (T-Labs Series in Telecommunication Services,, 2018)
This book describes an extension of the user behaviour simulation (UBS) of an existing tool for automatic usability evaluation (AUE). This extension is based upon a user study with a smart home system. It uses technical-sociological methods for the execution of the study and the analysis of the collected data. A comparison of the resulting UBS with former UBSs, as well as the empirical data, shows that the new simulation approach outperforms the former simulation. The improvement affects the prediction of dialogue metrics that are related to dialogue efficiency and dialogue effectiveness. Furthermore, the book describes a parameter-based data model, as well as a related framework. Both are used to uniformly describe multimodal human-computer interactions and to provide such descriptions for usability evaluations. Finally, the book proposes a new two-stage method for the evaluation of UBSs. The method is based on the computation of a distance measures between two dialogue corpora and the pair-wise comparison of distances among several dialogue corpora.